Aboriginal Two-Spirit and LGBTQ mobility: meanings of home, community and belonging in a secondary analysis of qualitative interviews - Passante, Lisa (2012)
This thesis reports on a secondary analysis of individual and focus group interviews from the Aboriginal Two-Spirit and LGBTQ Migration, Mobility and Health research project (Ristock, Zoccole, and Passante, 2010; Ristock, Zoccole, & Potskin, 2011). This was a community-based qualitative research project following Indigenous and feminist methods, involving two community Advisory Committees, and adopting research principles of Ownership Control Access and Possession (OCAP) (First Nations Centre, 2007). This analysis reviews data from 50 participants in Winnipeg and Vancouver and answers: How do Aboriginal Two-Spirit and LGBTQ people describe home, community and belonging in the context of migration, multiple identities, and in a positive framework focusing on wellbeing, strengths and resilience? Findings demonstrate how participants experience marginalization in both Aboriginal and gay communities. Their words illustrate factors such as safety required to facilitate positive identities, community building, belonging, and sense of home. For participants in this study home is a place where they can bring multiple identities, a geographical place, a physical or metaphorical space (with desired tone, feeling), and a quality of relationships. Community is about places, relationships, participation, and shared interests. Belonging is relational and interactive, feeling safe, accepted, and welcome to be yourself. Detractors interfere with positive meaning making and are identified in examples of contemporary effects of historical trauma. Also included are participant recommendations for community building, descriptions of holistic wellbeing, and examples of many ways urban Aboriginal Two-Spirit and LGBTQ people are creating communities of Two-Spirit vitality and resurgence (Simpson, 2011). May 2012